Sustainable Development for Future Generations: Economic Priorities - S. N. Bobylev (Мир новой экономики)
The article deals with the new challenges of transition to sustainable development in the world and Russia. Analyzes the long-term goals of sustainable development for Russia, the role of ecosystem services in the world and the country, indicators of sustainable development, the transition to green economy. For greater stability, you can not increase the amount of natural resources and at the same time increase the level of material well-being of the population due to the policy of “win-win” and the decoupling effect. The country needs a federal compensation ecological and economic mechanism that would take into account the value of regional ecosystems and their ecosystem services for the country and all mankind. It is important to support the transition to a model of green economy, which is largely due to the economic modernization objectives. Taking into account national priorities and features Russia needs to develop a system of sustainable development indicators.